Designing hybrid spaces for learning in higher education health contexts - Green JK (Springer Nature, 2021)
In Aotearoa New Zealand, undergraduate, professional health courses include social work, nursing, and biosciences courses that focus on learning how to support people with physical, mental, spiritual, and psychosocial/relational health and well-being concerns. Recently, the need for a nuanced understanding of how technologies might extend students’ experiences across and beyond physical classrooms has emerged. Drawing on contemporary ecological perspectives in education, this paper emphasises that design for learning involves a complex web of elements. Anchored in practice theory, the paper uses the analytical lens of the Activity-Centred Analysis and Design (ACAD) framework to explore how tools, tasks, and various social arrangements influence student learning activity. A multiple case study investigated the experiences and insights of five higher education teacher-designers, discussing the relationship between features of course design and their perceived impact on emergent learning activity. Design elements are also discussed in relation to the experience of teacher-designers adapting and transitioning to hybrid environments during Covid-19, whilst working with diverse learners in different contexts and disciplines. Interviews with teacher-designers revealed what they believe contributes to productive learning activity, such as the importance of creating safe learning environments, an overall appreciation for the opportunity to use technology for teaching and learning, and their use of a heutagogical approach, which emphasizes the development of knowledge and skills for teaching in hybrid learning environments. The paper argues for practical and targeted support to acknowledge, encourage, and enhance teacher-designers’ capabilities for transformational use of hybrid learning environments in health education.
Keywords: ACAD Framework; Health education; Higher education; Hybrid learning design; Undergraduates; Quality education